2015
DOI: 10.1002/advs.201500072
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation and Push‐Out Process with Spinel‐to‐Rocksalt Transition on Mg Insertion into Spinel Oxides in Magnesium Batteries

Abstract: On the basis of the similarity between spinel and rocksalt structures, it is shown that some spinel oxides (e.g., MgCo2O4, etc) can be cathode materials for Mg rechargeable batteries around 150 °C. The Mg insertion into spinel lattices occurs via “intercalation and push‐out” process to form a rocksalt phase in the spinel mother phase. For example, by utilizing the valence change from Co(III) to Co(II) in MgCo2O4, Mg insertion occurs at a considerably high potential of about 2.9 V vs. Mg2+/Mg, and similarly it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
207
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(226 citation statements)
references
References 29 publications
7
207
1
2
Order By: Relevance
“…Besides these batteries, many new types of batteries are being researched aiming at developing low cost and long lifetime technologies for largescale energy storage. [3][4][5][6][7][8] As shown in Table 1, the states of the electrode in typical batteries are solid and liquid with the possibility of gas state, and the states of the electrolyte are liquid and solid. Batteries with liquid metal electrodes (LMEs) are easy to scale up, usually have low cost and long cycle life, thanks to the conductive and amorphous liquid metal electrode structure.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these batteries, many new types of batteries are being researched aiming at developing low cost and long lifetime technologies for largescale energy storage. [3][4][5][6][7][8] As shown in Table 1, the states of the electrode in typical batteries are solid and liquid with the possibility of gas state, and the states of the electrolyte are liquid and solid. Batteries with liquid metal electrodes (LMEs) are easy to scale up, usually have low cost and long cycle life, thanks to the conductive and amorphous liquid metal electrode structure.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, several studies have claimed intercalation of Mg 2+ into spinel-structured Mn2O4 (λ-MnO2) in aqueousenvironments, 43,56 but the mechanism of the Mg insertion reaction into spinel-type Mn3O4 have not been ascertained. The results of Cabana et al 43 provided direct visu- 56 demonstrated that the Mg insertion into spinel lattices occurs via an "intercalation and push-out" process. The Mg 2+ cation is inserted into an octahedral site-16c, and the original cation located in the neighboring tetrahedral site-8a migrates to an adjacent 16c site due to the repulsion between the cations.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Okamoto et al [230] used a combination of electrochemical, structural, and ab initio analyses to study several spinels (MgCo 2 O 4 , MgMn 2 O 4 , MgFe 2 O 4 , MgCrO 2 , and Co 3 O 4 ), and suggest spinel MgMn 2 O 4 may be a viable above-room-temperature (150°C) MIB cathode material. The operating temperature was selected to improve solid state diffusion and accommodate the ionic liquid electrolyte (Cs-bis(trifluoromethane sulfonyl)amide (TFSA)), whose melting point is 120°C.…”
Section: Science China Materialsmentioning
confidence: 99%